2022
DOI: 10.56521/manajemen-dirgantara.v15i2.760
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Motivasi Kerja Dan Kepuasan Kerja Terhadap Peningkatan Kinerja Karyawan Melalui Komitmen Organisasi Pada Umkm (Studi Pada Umkm Paguyuban Keripik Tempe Sanan Kota Malang)

Abstract: Pengusaha di Asosiasi Keripik Tempe Sanan Kota Malang perlu memperhatikan kebahagiaan kerja, motivasi kerja, dedikasi organisasi, dan kinerja karyawan. Proses peningkatan kinerja pekerja sangat penting. Prosedur ini sangat penting bagi reputasi perusahaan, yang sama pentingnya dengan kepentingan keuangan perusahaan. Karena kepuasan kerja terkait dengan keterlibatan dan retensi karyawan, ini merupakan faktor penting bagi bisnis untuk dipertimbangkan. Dedikasi organisasi pada UMKM Paguyuban Keripik Tempe Sanan K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…In contrast, job resources such as autonomy and feedback positively correlated with employee engagement. Employee Motivation is critical to employee performance and organizational success [33]. Motivated employees are more likely to be productive, innovative, and committed to achieving organizational goals.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, job resources such as autonomy and feedback positively correlated with employee engagement. Employee Motivation is critical to employee performance and organizational success [33]. Motivated employees are more likely to be productive, innovative, and committed to achieving organizational goals.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Research has identified several factors that influence employee satisfaction, including job characteristics, organizational culture, leadership, and social support [12], [22], [23], [29], [52], [53]. Job characteristics, such as task variation, autonomy, and feedback, were found to have a positive relationship with employee satisfaction [28], [33], [54], [55]. Organizational culture, including values, norms, and beliefs, was also found to have a positive relationship with employee satisfaction [29], [44], [56].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…In their opinion, they are more important in coming up with novel ideas and accomplishing organizational objectives [23]. Effective teamwork and creativity are essential components in an entrepreneurial business setting for adapting to shifting consumer needs and market shifts [24]- [26].…”
Section: Introductionmentioning
confidence: 99%